2016
DOI: 10.1200/jco.2016.66.7881
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effectiveness of Neutropenic Diet and Social Restrictions as Anti-Infective Measures in Children With Acute Myeloid Leukemia: An Analysis of the AML-BFM 2004 Trial

Abstract: Purpose Although nonpharmacologic anti-infective measures are widely used in children treated for acute myeloid leukemia (AML), there is little evidence of their effectiveness. Patients and Methods We analyzed infectious complications in children during intensive treatment of AML according to the AML-BFM 2004 trial and surveyed sites on institutional standards regarding recommended restrictions of social contacts (six items), pets (five items), and food (eight items). A scoring system was developed with a rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 39 publications
1
35
0
1
Order By: Relevance
“…Evidence supporting food restrictions in patients with cancer in general is, however, ambiguous and limited to small studies (van Dalen et al , ). A recent study among different hospitals worldwide, many of them affiliated to a study group included in our survey, showed no beneficial effects of strict food regimens during AML treatment (Tramsen et al , ). Multiple groups emphasize limiting visits to day‐care and (indoor) crowded places.…”
Section: Discussionmentioning
confidence: 83%
“…Evidence supporting food restrictions in patients with cancer in general is, however, ambiguous and limited to small studies (van Dalen et al , ). A recent study among different hospitals worldwide, many of them affiliated to a study group included in our survey, showed no beneficial effects of strict food regimens during AML treatment (Tramsen et al , ). Multiple groups emphasize limiting visits to day‐care and (indoor) crowded places.…”
Section: Discussionmentioning
confidence: 83%
“…29 This result in combination with previous similar observations argues for a less strict use of neutropenic diets. [59][60][61][62][63][64][65][66][67] Therefore, focusing on safe food-handling practices and retaining restrictions on raw meat or dairy products, as well as apparent fungal components as mold cheese, but allowing raw fruit and vegetable if properly washed and/or peeled seems adequate. 61,68 Again, only adequately powered randomized controlled studies will give better evidence on effectiveness of food safety guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Other general measures, such as diet and avoiding social contacts and pets, are not proven to be effective (Tramsen et al, 2016). In general, one should distinguish general measures from interventions that are more dependent on type of microorganism.…”
Section: Infectionsmentioning
confidence: 99%
“…Strict hygiene has been proven to prevent transmission of infections from patient to patient in the hospital setting. Other general measures, such as diet and avoiding social contacts and pets, are not proven to be effective (Tramsen et al, 2016). Given the social consequences, it is doubtful whether it is justified to recommend them without the evidence supporting it.…”
Section: Infectionsmentioning
confidence: 99%